The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7547/15-036
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of the Flexor Tendon Repair Using Human Amniotic Membrane

Abstract: The results of this study show that the modified Kessler repair can be reinforced effectively with human amniotic membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…An alternative to amnion-derived cells, human amniotic membrane (HAM) is a more conveniently obtainable source which has been used in burn patients and to prevent peritendinous adhesions 45 . Dogramaci et al have recently demonstrated favorable results following application of HAM in an ovine flexor tendon reinforced tendon repair.…”
Section: Current Cell-based Approachesmentioning
confidence: 99%
“…An alternative to amnion-derived cells, human amniotic membrane (HAM) is a more conveniently obtainable source which has been used in burn patients and to prevent peritendinous adhesions 45 . Dogramaci et al have recently demonstrated favorable results following application of HAM in an ovine flexor tendon reinforced tendon repair.…”
Section: Current Cell-based Approachesmentioning
confidence: 99%
“…23 In its early use as a intact membrane sheet, the AM has been suggested to reduce scar formation following digital flexor tendon repair. 24 In more-recent tendon repair studies, the amniotic membrane has been used as a two-dimensional support in animal models of tendon repair, 25,26 highlighting the membrane’s ability to enhance the mechanical properties of the repair without addressing its potential role in the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%